Апаратно-програмна реалізація системи збору даних для імпульсного спектрометра ЯКР - Саміла, А.П. (Технология и конструирование в электронной аппаратуре, 2017)
Запропоновано апаратно-програмну реалізацію компактної системи збору даних для імпульсного спектрометра ядерного квадрупольного резонансу, апаратні рішення якої базуються на мультипротокольному USB245 FIFO перетворювачу FT2232H, що забезпечує передавання даних зі швидкістю до 480 Мб/с. З використанням засобів графічного об’єктно орієнтованого програмування синтезовано віртуальний інструмент LabVIEW для візуалізації та оброблення даних сигналів ядерної спінової індукції. Предложена аппаратно-программная реализация компактной системы сбора данных для импульсного спектрометра ядерного квадрупольного резонанса, аппаратные решения которой базируются на мультипротокольном USB245 FIFO преобразователе FT2232H, что обеспечивает передачу данных со скоростью до 480 Мб/с. С использованием средств графического объектно ориентированного программирования синтезирован виртуальный инструмент LabVIEW для визуализации и обработки данных сигналов ядерной спиновой индукции. A hardware and software implementation of compact data acquisition system for pulsed nuclear quadrupole resonance spectrometer is proposed. The developed system is based on multi-protocol converter USB-245FIFO FT2232H, which provides data transfer speeds up to 480 Mb/s. For nuclear spin induction visualization and data signal processing using graphical tools of the object oriented programming a LabVIEW virtual instrument is synthesized. To synchronize data acquisition system with start of the exciting pulse the FPGA configuration structure is developed. The experimental results are showed possibility of the broadband nuclear quadrupole resonance spectrums imaging with frequency resolution 1.6 kHz, which confirms the high accuracy of the developed data acquisition system. Two-channel transmitter provides simultaneous operation of the two independent data channels in a single hardware USB interface. The use of the proposed data acquisition system for portable nuclear quadrupole resonance spectrometers will significantly reduce the cost of laboratory equipment for radio physical experimentation.